Common pathways for primary hypertrophic and dilated cardiomyopathy - Kroumpouzou, E; Gomatos, I P; Kataki, A; Karayannis, M; Dangas, G D; Toutouzas, P (Hybridoma and hybridomics, 2003)
Testing the hypothesis that hypertrophic and dilated cardiomyopathy as well as viral myocarditis share a common mitogenic growth response pathway with mitotically competent cell types are the aims of this study. The expression of the c-fos, H-ras and c-myc genes was immunohistochemically determined in biopsies from 12 patients with dilated cardiomyopathy, 24 patients with hypertrophic cardiomyopathy, and 4 patients with myocarditis. Normal myocardium from 9 subjects was used as the control group. Staining results were correlated with patient's demographic data. C-fos, H-ras and c-myc protein overexpression was seen in 15 patients (62.5%) with primary hypertrophic and 4 patients (33.3%) with dilated cardiomyopathy. The majority of hypertrophic and dilated cardiomyopathy patients expressed at least one of the genes studied compared with the control group (p = 0.006). Primary cardiomyopathy patients also showed a statistically significant difference in the gene co-expression compared with the control group (p = 0.042). C-fos, H-ras, and C-myc protein expression did not differ substantially between patients with hypertrophic and dilated cardiomyopathy. Patients with myocarditis expressed only the C-fos protein (n = 2, 50%). C-fos, h-ras and c-myc genes are overexpressed in patients with cardiac hypertrophy and cardiac dilation. Cardiac myocytes respond to biomechanical stress by initiating several different processes. One of them is oncogene expression. This results in a hypertrophy of the myocytes proportional in length and width (hypertrophic cardiomyopathy or with a relatively greater increase in length than in the width (dilated cardiomyopathy).